2012
DOI: 10.1103/physrevb.85.165320
|View full text |Cite
|
Sign up to set email alerts
|

Diamagnetism and flux creep in bilayer exciton superfluids

Abstract: We discuss the diamagnetism induced in an isolated quantum Hall bilayer with total filling factor ν T = 1 by an in-plane magnetic field. This is a signature of counterflow superfluidity in these systems. We calculate magnetically induced currents in the presence of pinned vortices nucleated by charge disorder, and we predict a history-dependent diamagnetism that could persist on laboratory time scales. For current samples, we find that the maximum in-plane moment is small, but with stronger tunneling the momen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Interesting theoretical predictions concern the response of the bilayer exciton condensate to external electromagnetic fields [16,121,249,67] and impurities [66], as well as the transport properties of hybrid circuits including exciton condensates and superconductors [62,197,248]. For weak inter-layer interaction or filling factors other than ν T = 1, bilayers are predicted to undergo phase transitions to other strongly correlated phases, such as paired two-dimensional Laughlin liquids and Wigner solids [290], or peculiar excitonic charge density waves [48].…”
Section: Permanent Exciton Condensation In Bilayersmentioning
confidence: 99%
“…Interesting theoretical predictions concern the response of the bilayer exciton condensate to external electromagnetic fields [16,121,249,67] and impurities [66], as well as the transport properties of hybrid circuits including exciton condensates and superconductors [62,197,248]. For weak inter-layer interaction or filling factors other than ν T = 1, bilayers are predicted to undergo phase transitions to other strongly correlated phases, such as paired two-dimensional Laughlin liquids and Wigner solids [290], or peculiar excitonic charge density waves [48].…”
Section: Permanent Exciton Condensation In Bilayersmentioning
confidence: 99%
“…So there is an essential difference between the electric dipole superconductor and the exciton superfluid. In addition, a few previous works have investigated the dipole superfluid 16 17 30 31 . For example, Balatsky et al investigated the bilayer exciton system under an in-plane magnetic field and found that the phase of the condensate can couple to the gradient of the vector potential.…”
mentioning
confidence: 99%